Explaining the features of patient education in home care units in Iran: A qualitative study - Azar Darvishpour; Shiva Mahdavi (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: In recent years, health policies have emphasized accelerating patients' discharge from hospitals and receiving health care at home. The present study aimed to identify the characteristics of patient education in home care units in Iranian hospitals in 2021. MATERIALS AND METHODS: This descriptive, qualitative study was conducted on eight supervisors, 15 clinical nurses, and four home care nurses working in East Guilan hospitals. Semi-structured interviews were used to collect data. Interviews were conducted using guiding questions. Data were analyzed using conventional qualitative content analysis by MAXQDA 2007 software. RESULTS: Data analysis led to the emergence of 58 primary codes and six categories with the titles of "Education based on the expertise and clients' needs," "Emphatic nature of education," "Empowering clients to perform self-care programs," "Increasing the quality of clinical services," "Cost-effective education," and "Requirements for promoting the educational performance of home care units." The sixth category consists of four subcategories (tariffing insurance, continuous education of clients from the time of hospitalization not merely at the time of discharge, the existence of a monitoring system, and advertising and media coverage of the educational performance of the home care unit). CONCLUSIONS: The analysis of data showed that the education provided to patients in home care units is economically viable and empowers clients to self-care and increases the quality of clinical services. Due to the novelty of home care in Iran, it is necessary to pay more attention to the issues mentioned in this paper by managers and health policymakers.